MEMERIKSA KEMBALI (LOOKING BACK) PEMECAHAN MASALAH MATEMATIS MENGGUNAKAN WEBSITE WOLFRAMALPHA PADA MATERI INTEGRAL TAK TENTU (CV. ADIBA AISHA AMIRA, 2022)
Mathematical problem solving can be done with four stages, namely understanding the problem, making a plan, executing a plan and looking back. The purpose of this paper is to describe the process of looking back at mathematical problem solving using the wolframalpha website. The results showed that re-examining can be done in various ways including asking teachers, asking friends who are mathematically higher or using technology. One technology that can be used as a tool to check back is the Wolframalpha application.